2008
DOI: 10.1186/1471-2458-8-27
|View full text |Cite
|
Sign up to set email alerts
|

Systematic screening for unsafe driving due to medical conditions: Still debatable

Abstract: Background: Assessing people's ability to drive has become a public health concern in most industrialized countries. Although age itself is not a predictive factor of an increased risk for dangerous driving, the prevalence of medical conditions that may impair driving increases with age. Because the implementation of a screening for unsafe driving due to medical conditions is a public health issue, its usefulness should be judged using standardised criteria already proposed for screening for chronic disease. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
(84 reference statements)
0
13
0
2
Order By: Relevance
“…Ideally, we need to identify drivers with an increased risk of road traffic accidents due to a medical condition. In a previous paper,9 we proposed a general adaptation of the framework developed by the WHO for judging the relevance of a screening programme 6. We have suggested that four of the criteria (severity of the consequences for public health, definition of an adequate preclinical phase, accuracy and reliability of tests in the clinical phase, and efficacy of early intervention) should be modified for judging the relevance of systematic assessment of fitness to drive in relation to medical disorders (table 1).…”
Section: Assessing the Usefulness Of Early Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, we need to identify drivers with an increased risk of road traffic accidents due to a medical condition. In a previous paper,9 we proposed a general adaptation of the framework developed by the WHO for judging the relevance of a screening programme 6. We have suggested that four of the criteria (severity of the consequences for public health, definition of an adequate preclinical phase, accuracy and reliability of tests in the clinical phase, and efficacy of early intervention) should be modified for judging the relevance of systematic assessment of fitness to drive in relation to medical disorders (table 1).…”
Section: Assessing the Usefulness Of Early Detectionmentioning
confidence: 99%
“…We have suggested that four of the criteria (severity of the consequences for public health, definition of an adequate preclinical phase, accuracy and reliability of tests in the clinical phase, and efficacy of early intervention) should be modified for judging the relevance of systematic assessment of fitness to drive in relation to medical disorders (table 1). 9…”
Section: Assessing the Usefulness Of Early Detectionmentioning
confidence: 99%
“…The inclusion of the above variables is justified by the known influence of one's lifestyle and health-related factors on sleep as well as on driving (e.g., Barrash et al, 2010;Leproust et al, 2008;Verster et al, 2004). Individual height and weight measurements were used to calculate Body Mass Index (BMI).…”
Section: Control Variablesmentioning
confidence: 99%
“…In recent years, there has been a sudden increase in exposure to motor vehicles almost anywhere in the world, causing transport-related injuries (TRIs) the dominant mechanism of trauma in most parts of the world [5]. The global rank of our country, Iran, for accident-related mortality rate is eight while its position in the Eastern Mediterranean Region is two-the only second to Libya.…”
Section: Introductionmentioning
confidence: 99%